The Effectiveness of Tera Exercises to Reduce Musculoskletal Discomfort Elderly at Posyandu Warna Sari, Desa Glonggong Kecamatan Nogosari, Kabupaten Boyolali - Hastuti, Lis Sarwi (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: Everyone experiences musculoskeletal discomfort, and this problem will get worse with age, due to changes in the musculoskeletal system. Physical exercise is considered an effective non-pharmacological approach to reduce musculoskeletal complaints. Tera exercise is an aerobic exercise (using oxygen) because this exercise has an element of breathing exercise (breath training). Objectives: This study aims to determine the effectiveness of tera exercise to reduce musculoskeletal discomfort in the elderly at Posyandu Warna Sari, Glonggong Village, Nogosari District, Boyolali. Methods: This study uses quantitative research using pre-experimental design methods. The research design used in this study is one group pre-test and post-test design. Respondents were 18 elderly with ages ranging from 55 to 75 years in Posyandu Warna Sari, Desa Glonggong, Kecamatan Nogosari, Boyolali. The instrument used is the Nordic Body Map (NBM) used to measure subjectively the musculoskeletal discomfort. The treatment given is tera gymnastics given as many as 12 sessions and each session lasts for 30-40 minutes. Data analysis techniques using the Paired Sample T Test. Result: The calculated t result for the tera exercise intervention was 10.32 with a significance value (Pvalue) of 0.001. . Because the significance value is <0.05, there is a significant difference in the pre-test scores compared to the post-test scores for the respondents' musculoskeletal discomfort, so that Ha is accepted, namely Tera exercise is effective in reducing musculoskeletal complaints in the elderly at Posyandu Warna Sari, Desa Glonggong , Kecamatan Nogosari, Kabupaten Boyolali. Conclusion: Tera exercise is effective in reducing musculoskeletal discomfort in the elderly at Posyandu Warna Sari, Desa Glonggong, Kecamatan Nogosari, Kabupaten Boyolali. Keywords : Elderly, Tera Exercises, Musculoskeletal Discomfort